2009
DOI: 10.1186/1478-4491-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Task-shifting HIV counselling and testing services in Zambia: the role of lay counsellors

Abstract: Background: The human resource shortage in Zambia is placing a heavy burden on the few health care workers available at health facilities. The Zambia Prevention, Care and Treatment Partnership began training and placing community volunteers as lay counsellors in order to complement the efforts of the health care workers in providing HIV counselling and testing services. These volunteers are trained using the standard national counselling and testing curriculum. This study was conducted to review the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 4 publications
6
81
0
Order By: Relevance
“…Skill at HIV testing among lay counsellors was found to be satisfactory, which is consistent with results reported by other investigators in Zambia (Sanjana et al, 2009). While many have wondered at the quality of HIV testing done by members of the community, the 99.2% HIV testing concordance rate with panel samples in the current study provides support for task-shifting initiatives in this area.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Skill at HIV testing among lay counsellors was found to be satisfactory, which is consistent with results reported by other investigators in Zambia (Sanjana et al, 2009). While many have wondered at the quality of HIV testing done by members of the community, the 99.2% HIV testing concordance rate with panel samples in the current study provides support for task-shifting initiatives in this area.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, although Sanjana et al, (2009) reported that lay counsellors with approved training can play a major role at health facilities to provide counselling and testing services of quality, the systematic monitoring of performance of lay counsellors was lacking. The National Quality Assurance Strategy for Counselling and Testing recommended the re-testing of 10% of specimens using dried blood spots (DBS), on-site monitoring, and proficiency testing using a panel of specimens with known reactivity(Ministry of Health, 2007), thought it has yet to be fully implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Looking across sectors, studies from Australia [67], Kenya [72] and the UK [68], as well as an international review [69] suggest providing appropriate community-based care can address some conditions comparably to hospital care with fewer resource requirements. Countries such as Kenya [72], Zambia [75,77] and Zimbabwe [78], lacking the resources to formally train and/or retain sufficient numbers of nurses and other health professionals, have found certain health care services can be provided effectively by shifting some tasks from doctors and nurses to personnel with less formal training. This would enable the more scarce professionals to focus on more complex care.…”
Section: Increased Rn Productivitymentioning
confidence: 98%
“…The level of education for most of these educators who were implementing this project was secondary school. Human resource shortage has placed a heavy burden on the few health care workers available at designated health facilities in our country [7].…”
Section: Introduction Issn: 2454-499xmentioning
confidence: 99%